Faktor-faktor yang mempengaruhi keputusan menggunakan internet banking nasabah bank BRI di Surabaya - Novela Rizki Lestari (Journal of Business & Banking, 2018)
The global economy increase the competition in the banking secotrs. For that reason, it is important to see the factors that can increase the users of the customer of internet banking. The purpose of this study was to examine the effect of perceptions of usability, perceivedease, and security problems on the decision to use internet banking for customers of BRI Bank Surabaya. The sample of this research consists of Bank BRI customers. They were taken by using a judgment sampling method which is based on certain criteria. The data were collected from 74 respondents. The analytical method used in this study is multiple linear regression with SPSS. The results show that perception of usability and perceived ease and security issues have a signifi cant and positive effect on customer decisions in using Bank BRI internet banking in Surabaya.